ENVIRONMENTAL IMPACTS CAUSED BY PADDY FIELD MANAGEMENT - V. V. N. Murty; N. Cao Don; H. Araki (Lowland Technology International, 2009)
Paddy fields occupy large areas and are an important component of the cropped areas in the Asian Region. In this study, the environmental impacts caused by paddy field management are investigated and studied. It is observed that paddy fields cause both beneficial and adverse effects on the environment. The beneficial effects consist of flood retardation, sediment retention and recharge to groundwater. Important adverse effects are contamination to water resources, effect on human health and methane emissions. Steps needed to mitigate the adverse effects from paddy fields are also considered. These include understanding the water balance components for efficient water management, provision of surface and subsurface drainage systems and recirculation of drainage water. Water quality aspects, which need to be considered while recirculation drainage water and final disposal of the drainage water, are also studied. While all aspects of water quality are important, in general water quality aspects, which need attention, appear to be the total nitrogen and pesticide residues. Further studies are needed to manage both these constituents of the drainage water.